Kontribusi Rihlah Ilmiah Ibnu Battuta terhadap Sumber Penulisan Sejarah Islam - Andi Lifiani Ansar; Nuraeni S; Ibrahim, Ishauddin (Rihlah : Jurnal Sejarah dan Kebudayaan, 2024)
This research is based on Ibn Battuta's journey from the African continent to Southeast Asia in 1333-1345 AD. On this journey, he witnessed many important Islamic events in the Middle Ages. On that basis, the purpose of the research is to find out how and what impacts and results Ibn Battuta obtained from the journey. The data collection technique for this research is through library sources. The approach used is a historical, religious and sociological approach with historical research steps, namely heuristics, source criticism, interpretation, and historiography so that the results of the study show that Ibn Battuta was a faqih, he was a knowledgeable, persistent and evaluative person who had a background in a family of legal experts, Ibn Battuta managed to reach the Delhi Sultanate in India and occupy an important position in the Islamic kingdom and with the provision of knowledge, faith, experience and courage, he was then sent by the Delhi Sultanate to become a diplomatic ambassador in the Yuan Dynasty empire and proved that the conditions of the Middle Ages could be conveyed in detail through a work written by Ibn Juzay which was dictated directly by Ibn Battuta so that the work became one of the references for historical sources in the present day.